2015
DOI: 10.15837/ijccc.2015.6.2081
|View full text |Cite
|
Sign up to set email alerts
|

PI and Fuzzy Control for P-removal in Wastewater Treatment Plant

Abstract: Due to the complex and non linear character, wastewater treatment process is difficult to be controlled. The demand for removing the pollutant, especially for nitrogen (N) and phosphorus (P), as well as reducing the cost of wastewater treatment plant is an important research theme recently. Thus, in this paper, the benchmark proposed default control strategy and 10 additional control strategies are applied on the combined biological P and N removal Benchmark Simulation Model No.1 (BSM1-P). In addition, accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 20 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The higher‐level control loops compute optimized set points (Guerrero, Guisasola, Comas, Rodríguez‐Roda, & Baeza, 2012; Guerrero, Guisasola, Vilanova, & Baeza, 2011; Rojas, Baeza, & Vilanova, 2011). (Xu & Vilanova, 2013; 2015; Hongyang et al, 2018) used BSM1‐P as a simulation platform and used three different control frameworks consisting of PI, Fuzzy, and MPC. These control strategies showed significant improvement in the effluent quality with increased operating costs.…”
Section: Resultsmentioning
confidence: 99%
“…The higher‐level control loops compute optimized set points (Guerrero, Guisasola, Comas, Rodríguez‐Roda, & Baeza, 2012; Guerrero, Guisasola, Vilanova, & Baeza, 2011; Rojas, Baeza, & Vilanova, 2011). (Xu & Vilanova, 2013; 2015; Hongyang et al, 2018) used BSM1‐P as a simulation platform and used three different control frameworks consisting of PI, Fuzzy, and MPC. These control strategies showed significant improvement in the effluent quality with increased operating costs.…”
Section: Resultsmentioning
confidence: 99%
“…This is achieved by employing fuzzy rules that are identical to those used in human inference design. FLC is used on the WWTP in this study [19,23]. Figure S4 depicts the FLC controller in the wastewater flow diagram.…”
Section: Design Of Fuzzy-logic Controller (Flc)mentioning
confidence: 99%
“…Different plant-wide models are studied in the literature, which includes sludge control approaches, biogas production in primary settler, handling of the anaerobic digester, and phosphorus modeling with interactions of sulfur and iron cycles [10][11][12][13][14][15][16][17]. In the literature, many control applications like fuzzy logic controller (FLC), model predictive controller (MPC), proportional-integral (PI), and ammonia-based aeration control (ABAC) with different hierarchical combinations of PI, MPC, and fuzzy were studied, and it is observed that there is a trade-off between operational cost and effluent quality [18][19][20][21]. Maheswari et al (2020) designed the nested control loop on three-stage biological treatment for ammonia changes and they observed that Effluent Quality Index (EQI) is improved with higher operational costs [22].…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 3 illustrates the process of obtaining z output from a Mamdani two-rule fuzzy inference system with 2 inputs, x and y [18] [16]. There are several defuzzification methods, including center of area (COA) or centroid, center average, maximum membership principle, and min-max membership (middle of maxima) [6].…”
Section: 3mentioning
confidence: 99%